The Practice of Fiscal Citizenship - Ana Maria da Costa Porto; Antônio de Moura Borges (Revista Brasileira de Direitos e Garantias Fundamentais, 2016)
The citizen is not always aware of his tax rights and obligations, lacking awareness of the exercise of fiscal and tax citizenship. This article presents an analysis of the importance of the citizen to be informed about the embedded taxes when purchasing goods and providing services, as well as the way tax expenditures are made, so that he acquires an active and participatory citizenship for the purpose of achieving fiscal citizenship.